A WEBSITE-BASED INFORMATION SYSTEM DEVELOPMENT FOR APPLYING TEMPORARY AIRPORT PASS REGISTRATION - Adilia Parmono, Zalzariana; Parjan, Parjan; Andayani, Thursina; Azzahra, Vania Nadhifa; Akaike, Hideo (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Pass visitor is an entry permit used by guests (visitors) who carry out visits or activities at the airport, and the management and registration process for applying is still done manually. This research aims to build a website-based application for registered pass visitors and conduct black box testing. The research and development (R&D) method uses the System Life Development Cycle (SDLC) technique with waterfall as a development model that involves analysis, design, implementation, and testing. Data collection by conducting observation and document analysis. The result is a website-based application that is designed using Google Apps Script. This application has been validated by a media design expert with a validation result of 82.10% and a material expert with a validation result of 86.25% with the category